Evolution of Sustainability Reporting Frameworks - Iulia-Diana COSTEA; Camelia-Daniela HATEGAN (Audit Financiar)
This research paper offers an extensive overview of the evolution of sustainability reporting practices, from the use of several frameworks by companies across the European Union, to the transition to a single regulation: the European Sustainability Reporting Standards. The article aims to expand the research conducted in sustainability reporting by narrowing and focusing only on a five-year time period. The analysis encompasses a bibliometric examination of a sample of more than 1,000 articles from Web of Science over a time-horizon of five years using VOSviewer software. The keywords selected as relevant for this research included phrases such as “sustainability reporting”, “ESG reporting”, “Corporate Social Responsibility Reporting” and “European Sustainability Reporting Standards”. The results of this research show a clear interest for sustainability information on all three components, E, S and G, but an insufficient number of articles on the transition to ESRS, its requirements and assurance practices regarding the accuracy and completeness of these reports. Possible limitations of this research may include the exclusion of other academic writing beyond the established time-horizon and utilization of only articles from only one database, Web of Science. Despite the abundance of research in the sustainability domain, this paper contributes to a clearer understanding of ESRS data-points and topics to be addressed by the companies that fall under the umbrella of the CSRD requirements.